Does psychological work environment matter? Relationship between psychological climate reflecting individual perception of work environment and stress among public servants - Vadym Mozgovoy (Cogent Business & Management, 2022)
This study examines how individual perceptions of the work environment reflecting the psychological climate could influence the stress felt by public servants. This study adopts a transactional perspective to argue that valuation of the work environment and the job itself influences the perception of potential stressors and hypothesizes the relationship between the self-engagement psychological climate, stress, and intention to stay in public service. The proposed hypotheses are validated through a cross-sectional survey of 332 public servants in Switzerland. First, the study finds that role clarity, contribution, and supportive management characterize the psychological climate of public servants. Second, the results of the multiple regression analysis indicate that the psychological climate reduces the felt stress with the highest impact of the role clarity. Third, mediation analysis indicates that the psychological climate mediates the relationship between intention to stay and stress. These findings suggest an important theoretical role for the work environment perception in alleviating stress. In practice, findings imply that public managers can foster a higher psychological climate by setting clear organizational roles and predictable task norms, as well as by providing opportunities for career development.
Keywords: 650; psychological climate; public management; stress; work environment